Solusi Cerdas Meningkatkan Produktivitas Pengrajin Maeswara dalam Pengolahan Limbah Eceng Gondok - Fitria Oktariani; Arif Rizkiawan Saputra; Fatimah Nur Hidayah; Fitria Ida Nurul Aini; Muhammad Alfarizi; Nur Kholifah (Jurnal Pengabdian Masyarakat, 2026)
Maeswara Basket is a business that transforms water hyacinth into various handicrafts. The manual flattening of water hyacinth fibers has proven to be less efficient and often results in inconsistent products. To solve this problem, we propose the use of flating machine technology that aims to simplify and speed up the production process, ensuring that each product is of consistent high quality. The methods used in the implementation of this program include: partner analysis, introduction of technological changes to partners, socialization and training on the use of tools to partners, analysis of machine feasibility, and also evaluation of activities. With the flating machine, Maeswara Basket hopes to increase production efficiency and quantity. Craftsmen, especially women's groups in Pengasih, will experience an increase in income thanks to better product quality and higher appeal to consumers. The application of this technology not only has a positive economic impact, but also strengthens cooperation and solidarity among artisans. With a more efficient production process and better results, Maeswara Basket is poised to grow and thrive, bringing benefits to the entire community.